3D joint inversion of gravity data and Rayleigh wave group velocities to resolve shear-wave velocity and density structure in the Makran subduction zone, south-east Iran. (15th April 2019) - Abdollahi, Somayeh; Zeyen, Hermann; Ardestani, Vahid Ebrahimzadeh; Shomali, Zaher Hossein
Graphical abstract: Highlights: Obtaining shear wave velocity structure images of the Makran subduction zone, south-east Iran. Constructing a new model of Moho depth in the Makran region. Achieving density structure images of the region. Abstract: In this study, we developed a method to invert jointly Rayleigh wave group velocities and gravity anomalies for velocity and density structure of the lithosphere. We applied the method to the Makran accretionary prism, SE Iran. The reason for using different data sets is that each of these data sets is sensitive to different parameters. Surface wave group velocities are sensitive mainly to shear wave velocity distribution in depth but do not well resolve density variations. Therefore, joint inversion with gravity data increases the resolution of density distribution. Our approach differs from others mainly in the model parameterization: Instead of subdividing the model into a large number of thin layers, we invert for the properties of only four layers: thickness, P- and S-wave velocities and densities and their vertical gradients in sediments, upper-crust, lower-crust and upper mantle. The method is applied first to synthetic models in order to demonstrate its usefulness. We then applied the method to real data to investigate the lithosphere structure beneath the Makran. The resulting model shows that Moho depth increases from Oman Sea (18–33 km) and Makran fore-arc (33–37 km) to the volcanic-arc (44–46 km). The crustal density is high in the Oman Sea as should be expected for the oceanic crust. We also find a high-velocity anomaly in the upper mantle under the Oman Sea corresponding to the subducting slab. The crust under the fore-arc, volcanic-arc and back-arc settings of Makran subduction zone is characterized by low-velocity zones.